Estimating evapotranspiration from paddy (Oryza sativa) field under humid tropical condition - Abdullahi, Abubakar Sadiq; Ahmad, Desa; Mohd Soom, Mohd Amin; Mohamed Shariff, Abdul Rashid (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Realistic estimate of evapotranspiration (ET) is a major factor in agricultural planning and determining crop production potential of a given region. It varies with crop growth stage. An assessment of water loss as evapotranspiration was conducted using field testing of a simplified, sensitive and accurate microlysimeter for ponded paddy field. A constant water level is maintained in the microlysimeter with a Marriott tube system and water losses from the manometer were measured. Daily variations of ET and deep percolation (DP) were determined in Peninsula Malaysia for main (August to December) and off (January to May) season cropping. Measured evapotranspiration values were compared between season and location. The average ET rates of rice growing areas are in the range of 3.3 – 6.2 and 4.6 – 6.5 mm day-1 for main and off season respectively. The relationships between ET and paddy growth period for the entire site had highly significant values with r2 > 83 %, and the DP is between 0.35 and 2.1 mm day-1. The study showed no significant difference in the rate of ET for both seasons and locations. The microlysimeter with the Marriott tube systems measures evapotranspiration on daily or hourly basis and can be fabricated locally.